2016
DOI: 10.1186/s12889-016-3289-1
|View full text |Cite
|
Sign up to set email alerts
|

“As soon as you’ve had the baby that’s it…” a qualitative study of 24 postnatal women on their experience of maternal obesity care pathways

Abstract: Background: Maternal obesity is associated with risks to mother and infant, and has implications for healthcare costs. United Kingdom (UK) levels of maternal obesity are rising, with higher prevalence in North East (NE) England, where this study was set. Pregnancy is often seen as an opportune time for intervention -a 'teachable moment' -which is ripe for promoting behaviour change. In response to rising obesity levels, a National Health Service (NHS) Foundation Trust in NE England implemented three maternal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 46 publications
(55 reference statements)
0
44
0
Order By: Relevance
“…13 However, women have highlighted a need for additional weight management support during the postpartum period as little is currently provided. 17,49,50 Systematic review evidence 49,[51][52][53][54] and the National Institute for Health and Care Excellence (NICE) public health guidance 45 both highlight gaps in knowledge about effective and appropriate weight management interventions for women during the postpartum period. There is systematic review evidence to suggest that diet and physical activity interventions delivered post partum have a moderate but positive influence on maternal weight, [51][52][53][54] and that interventions combining diet and activity behaviour change may be more successful, 49,52,53 as well as interventions that included selfregulatory behaviour change techniques (BCTs), such as self-monitoring of weight.…”
Section: Evidence-based Strategies To Support Postpartum Weight Managmentioning
confidence: 99%
“…13 However, women have highlighted a need for additional weight management support during the postpartum period as little is currently provided. 17,49,50 Systematic review evidence 49,[51][52][53][54] and the National Institute for Health and Care Excellence (NICE) public health guidance 45 both highlight gaps in knowledge about effective and appropriate weight management interventions for women during the postpartum period. There is systematic review evidence to suggest that diet and physical activity interventions delivered post partum have a moderate but positive influence on maternal weight, [51][52][53][54] and that interventions combining diet and activity behaviour change may be more successful, 49,52,53 as well as interventions that included selfregulatory behaviour change techniques (BCTs), such as self-monitoring of weight.…”
Section: Evidence-based Strategies To Support Postpartum Weight Managmentioning
confidence: 99%
“…In only one study, women believed it was the increased weight which inflated the risk and did not blame the provider's stigma [35]. As a result of these stereotyped attitudes and perceived judgements, women felt that they were 'boxed in' with other women affected by obesity [18,33,40], penalised for their weight [33,34] and blamed for complications which arose [29][30][31]33].…”
Section: Study Findings-themes For Perceptions Of Risk During Pregnanmentioning
confidence: 99%
“…Only one woman stated the opposite, because the counselling was "backed up by evidence" [41]. Another woman appreciated being identified within a group, because it made her feel that she was not at fault; risk happened to other women too [29].…”
Section: Study Findings-themes For Perceptions Of Risk During Pregnanmentioning
confidence: 99%
“…This is unfortunate since women who are aware of their own BMI and individual weight gain recommendations are more likely to gain adequate gestational weight (Shulman and Kottke, 2016;Whitaker et al, 2016). In some previous studies, pregnant women were positive to healthcare professionals bringing up weight (Atkinson et al, 2016;Dinsdale et al, 2016) and to being weighed (Brownfoot et al, 2016b;Heslehurst et al, 2017), while other studies showed that women with obesity wished that weight should not be in focus for caregivers, and perceived weight controls as uncomfortable (Nyman et al, 2010). These findings suggest a potential communication problem that is largely unexplored and may leave pregnant women unaware of risks with excessive gestational weight gain and thereby less able to make well-informed lifestyle choices (Christenson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%